Tree species is the major factor explaining C:N ratios in European forest soils - Cools, N.; Vesterdal, L.; De Vos, B.; Vanguelova, E.; Hansen, K.; Vos, B. De (Forest Ecology and Management, 2013)
The C:N ratio is considered as an indicator of nitrate leaching in response to high atmospheric nitrogen (N) deposition. However, the C:N ratio is influenced by a multitude of other site-related factors. This study aimed to unravel the factors determining C:N ratios of forest floor, mineral soil and peat top soils in more than 4000 plots of the ICP Forests large-scale monitoring network. The first objective was to quantify forest floor, mineral and peat soil C:N ratios across European forests. Secondly we determined the main factors explaining this C:N ratio using a boosted regression tree analysis (BRT), including fifteen site and environmental variables. Ninety-five percent of the C:N ratios were between 16 and 44 in the forest floor, between 13 and 44 in the peat topsoil and between 10 and 32 in the mineral topsoil. Within the aerated forest floor and the mineral soil, the C:N ratios decreased with depth, while in the hydromorphic forest floor and the peats no clear trend with depth was observed. Tree species was clearly the most important explanatory variable for the C:N ratio in both forest floors and topsoils, while it was soil type in the deeper mineral soil layers. The lowest C:N ratios both in the forest floor and the top mineral soil were found in black locust (Robinia pseudoacacia L.) and black alder (Alnus glutinosa L.) stands, both N fixing tree species. While in the forest floor the highest C:N ratios were found in evergreen species like pine, cork oak (Quercus suber L.) and eucalyptus, the pine species and Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) showed the highest C:N ratios in the mineral soil. The second most important explanatory variable in the forest floor and mineral topsoil was the biogeographical zoning (ecoregion). In the peat topsoil and in the deeper mineral soil layers it was the humus type. Deposition and climatic variables were of minor importance at the European scale. Further analysis for eight main forest tree species individually, showed that the influence of environmental variables on C:N ratios was tree species dependent. For Aleppo pine (Pinus halepensis Miller) and holm oak (Quercus ilex L.), both with a typical Mediterranean distribution, the relationship between N and S deposition and C:N ratio appeared to be positive. This study suggests that applying C:N ratios as a general indicator of the N status in forests at the European level, without explicitly accounting for tree species, is too simplistic and may result in misleading conclusions.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Carbon; Forest floor; ICP forests; Mineral soil; nitrogen; Tree species

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Leaf CO2 efflux is attenuated by acclimation of respiration to heat and drought in a Mediterranean tree - Rodriguez-Calcerrada, Jesus; Jaeger, Carsten; Limousin, Jean M; Ourcival, Jean M; Joffre, Richard; Rambal, Serge (Functional Ecology, 2011)
* 1Understanding the effect of water deficit on plant respiration and its temperature sensitivity at long time-scales is important for anticipating the shift in ecosystem dynamics that is expected to occur as a result of climate change. * 2We investigated seasonal variations of leaf dark respiration and sensitivity to temperature in the upper and lower canopy of Quercus ilex trees in a forest stand that had been exposed to either 33% throughfall reduction or normal rainfall for the preceding 6 years. * 3For upper and lower canopy leaves, light-saturated photosynthesis and respiration at a reference temperature of 15 °C (R15) had the lowest values in late summer, when both traits were lower in trees subjected to throughfall reduction than in those subject to control conditions. Respiration acclimated to seasonal shifts in temperature, more intensively through summer than winter and in throughfall-exclusion than control trees. Foliar concentration of soluble sugars was positively correlated with R15 across seasons. * 4As leaf respiration decreased with increasing water deficit, and the relationship between water status and respiration did not differ between trees that had been exposed to 7 years of enhanced drought when compared with controls, we suggest that drier conditions projected for the Mediterranean may attenuate the stimulation of leaf respiratory CO2 release by global warming in Q. ilex forests.
Keywords: abiotic factor; canopy depth; Carbon; drought acclimation; mediterranean habitat; nonstructural carbohydrates; thermal acclimation; throughfall exclusion

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Adsorption of Zn(II) in aqueous solution by activated carbons prepared from evergreen oak (Quercus rotundifolia L.). - Gómez-Tamayo, M Del Mar; Macías-García, Antonio; Díaz Díez, M Angeles; Cuerda-Correa, Eduardo M (Journal of hazardous materials, 2008)
In the present work activated carbons have been prepared from evergreen oak wood. Different samples have been prepared varying the concentration of the activating agent (H(3)PO(4)) and the treatment temperature. The yield of the process decreases with increasing phosphoric acid concentrations. Furthermore, high concentrations of activating agent lead to mainly mesoporous activated carbons to the detriment of the microporous texture. Treatment temperatures up to 450 degrees C lead to a progressive increase of the micro- and mesopore volumes. Values of specific surface area (S(BET)) as high as 1723 m(2) g(-1)have been obtained using appropriate phosphoric acid concentrations and treatment temperatures. The samples prepared have been successfully used in the removal of Zn(II) from aqueous solutions. From the adsorption kinetic data it may be stated that the equilibrium time is, in all cases, below 170 h. The adsorption process as a rule becomes faster as the mesopore volume and specific surface area of the samples increase. The adsorption isotherms in liquid phase point out that the adsorption capacity (n(0)(s)) and the affinity towards the solute (K(ci)) are higher for the sample showing the most developed mesoporous texture and surface area as well.
Keywords: Adsorption; Carbon; Carbon: chemistry; Hydrogen-Ion Concentration; Quercus; Solutions; Water Pollutants, Chemical; Water Pollutants, Chemical: chemistry; Water Purification; Water Purification: methods; Wood; Zinc; Zinc: chemistry

Modelling leaf mass per area in forest canopy as affected by prevailing radiation conditions - Davi, H.; Barbaroux, C.; Dufrêne, E.; François, C.; Montpied, P.; Bréda, N.; Badeck, F. (Ecological Modelling, 2008)
Leaf mass per area (LMA) is a key leaf trait, which conditions the assessment of carbon balance and the adaptation of the species to their environment. LMA decreases exponentially within the canopy at a lower rate coefﬁcient (kLMA) than the extinction coefﬁcient (kPAR) of photosynthetically active radiation (PAR); consequently the canopy is not fully optimized for the carbon balance. A new algorithm to simulate LMA in forest canopies is developed. The algorithm is based on a relationship between LMA of leaves at a given canopy depth and PAR, that they absorb, during leaf growth. The LMA sub-model is then tested against independent experimental data to demonstrate its validity to assess (i) the LMA vertical distribution inside the canopy, (ii) its evolution during the season and (iii) the variability observed between sites, years and species. Then, the LMA sub-model is coupled with a process-based model simulating carbon, water and energy balances in forest ecosystem. The coupled model is applied to a sensitive analysis for a case study in a beech forest.
Keywords: Carbon; Fagus sylvatica L.; Leaf mass per area; Modelling; Photosynthetically active radiation; Quercus ilex L.; Quercus petraea (Matt.) Liebl.

Modelling leaf mass per area in forest canopy as affected by prevailing radiation conditions - Davi, H.; Barbaroux, C.; Dufrêne, E.; François, C.; Montpied, P.; Bréda, N.; Badeck, F. (Ecological Modelling, 2008)
Leaf mass per area (LMA) is a key leaf trait, which conditions the assessment of carbon balance and the adaptation of the species to their environment. LMA decreases exponentially within the canopy at a lower rate coefﬁcient (kLMA) than the extinction coefﬁcient (kPAR) of photosynthetically active radiation (PAR); consequently the canopy is not fully optimized for the carbon balance. A new algorithm to simulate LMA in forest canopies is developed. The algorithm is based on a relationship between LMA of leaves at a given canopy depth and PAR, that they absorb, during leaf growth. The LMA sub-model is then tested against independent experimental data to demonstrate its validity to assess (i) the LMA vertical distribution inside the canopy, (ii) its evolution during the season and (iii) the variability observed between sites, years and species. Then, the LMA sub-model is coupled with a process-based model simulating carbon, water and energy balances in forest ecosystem. The coupled model is applied to a sensitive analysis for a case study in a beech forest.
Keywords: Carbon; Fagus sylvatica L.; Leaf mass per area; Modelling; Photosynthetically active radiation; Quercus ilex L.; Quercus petraea (Matt.) Liebl.

Effects of fire on soil carbon and nitrogen in a Mediterranean oak forest of Algeria - Rashid, G H (Plant and Soil, 1987)
The effects of wildfire on the dynamics of pH, organic C, total and mineral N and in vitro C and N mineralization were investigated in the soil under oak (Quercus suber L.) trees. Soil samples were taken from 5 to 21 months subsequent to the fire. The pH increased sharply in the burned surface soil (0-5 cm) taken 5 months after the fire and dropped only by half a unit over 14 to 21 months. However, at greater depth (5-15 cm), the burned soil was more acidic than the adjacent unburned soil up to 9 months following the fire, and thereafter its pH rose only slightly above that of the unburned soil. There were sharp rises in the concentration of organic C, total and mineral N in addition to in vitro mineralization activities in the burned surface soil collected 5 months after the fire; these dropped off in the subsequent samples approaching or falling below the values obtained in the unburned surface soil after 21 months. At a depth of 5-15 cm only slight or no increases over unburned soil were evident.
Keywords: Carbon; forest soil; mineralization; nitrogen; pH; Wildfire